Nivel de satisfacción de los usuarios de un establecimiento farmacéutico del Distrito de El Porvenir - Trujillo, Diciembre 2018 - Zavaleta Ventura, Lucy Victoria (2019)
This research work is a descriptive, cross-sectional and prospective study, with the objective of determining the level of satisfaction of the users of a private pharmaceutical establishment in the district of El Porvenir -Trujillo during the month of December 2018. The level of satisfaction, through a structured questionnaire according to the Likert scale to which 366 users whose ages fluctuate between 18-69 years of age responded; Then the correlation between the socio-demographic characteristics was determined: sex, age, degree of education and the level of satisfaction, and finally the dimensions of quality were correlated with overall satisfaction. 66% of the respondents were women, 52% of the users belonged to the age group 36-50 years and 40% of users presented a degree of technical higher education. The overall level of user satisfaction on a scale of 1 to 5 is 4.43 and the percentage of fully satisfied users is 99%. No correlation was found between socio-demographic characteristics: sex, age, degree of education and level of satisfaction